(untitled) (Prithvi Academic Journal, 2022)
This article aims to observe the various aspects shaping commercial bank profitability in Nepal. As determining factors, bank related and external macroeconomic variables that influence bank profitability were taken into account. A set of balanced panel data containing 13 Nepali commercial banks for 12-year period (2009-2020) with 156 observations was employed for analysis. Descriptive statistics and Pearson’s correlation analysis were employed to measure the status and explore the relationship between independent and dependent variables under study. The study findings were drawn using fixed-effect panel regressions. The study revealed that loan to deposit, known as credit-deposit ratio, has a significant positive impact on the return on assets and net interest margin of commercial banks. The growth of economic activities of the nation measured by gross domestic product growth, significantly influence profits. It implies that the increase in the nation’s economic activities leads to escalate the size of loans and advances and eventually earnings of the banks. However, non-performing assets weakly influence the return on assets, but it has a significant negative effect on the equity return. These outcomes proposed that commercial bank profitability can be increased by extending the degree of loan and advance relative to deposit and economic activities of the nation, and decreasing non-performing assets.